2000
DOI: 10.1111/j.1749-6632.2000.tb06922.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Characterization and Identification of γ‐Secretases Using Transition‐state Analogue Inhibitors

Abstract: The amyloid‐β protein (Aβ), strongly implicated in the etiology of Alzheimer's disease (AD), is formed from the amyloid‐β precursor protein (APP) through sequential proteolysis by β‐ and γ‐secretases. Cleavage by γ‐secretase takes place within the middle of the single transmembrane region of APP and results primarily in 40‐ and 42‐amino acid Aβ C‐terminal variants, Aβ40 and Aβ42. The latter form of Aβ is highly fibrillogenic, is invariably elevated in autosomal‐dominant forms of AD, and is the major Aβ compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…In addition, observation of this phenomenon in both cell culture systems and partially purified membrane preparations makes it unlikely that increased A␤42 production is a result of inhibitory effects on other intracellular processes (36,41). Interestingly, the degree of enhancement of A␤42 production elicited by ␥-secretase inhibitors is strongly correlated with their inhibitory potency (42), suggesting that increased A␤42 generation is mechanistically related to active site-directed inhibition.…”
Section: ␥-Secretase Inhibitors Mimic the Effects Of Pathogenic Ps Mumentioning
confidence: 85%
“…In addition, observation of this phenomenon in both cell culture systems and partially purified membrane preparations makes it unlikely that increased A␤42 production is a result of inhibitory effects on other intracellular processes (36,41). Interestingly, the degree of enhancement of A␤42 production elicited by ␥-secretase inhibitors is strongly correlated with their inhibitory potency (42), suggesting that increased A␤42 generation is mechanistically related to active site-directed inhibition.…”
Section: ␥-Secretase Inhibitors Mimic the Effects Of Pathogenic Ps Mumentioning
confidence: 85%
“…Taking advantage of in vitro presenilinase and -secretase activity assays that share the same conditions for de novo generation of PS NTF and CTF and the generation of A , parallel microsomes were treated with different -secretase inhibitors. Among a number of transition-state analogue inhibitors of -secretase that were shown to inhibit A generation [96][97][98], certainsecretase inhibitors can block presenilinase activity in vitro [90]. For example, some less potent -secretase inhibitors (MW167 and CM35) reduced PS1 fragment generation.…”
Section: Presenilinase and -Secretase Inhibitors: One Bird Two Stones?mentioning
confidence: 98%
“…In one study, the A␤ rise was reported in isolated membrane preparations, suggesting a direct effect of peptide aldehydes on ␥-secretase (6). Further evidence that ␥-secretase can mediate the A␤ rise comes from studies with difluoroketone-based inhibitors, which are selective for ␥-secretase and which cause a robust rise in A␤42 both in cell culture (11)(12)(13) and in isolated membrane-based assays (6). Furthermore a rise in total A␤, as well as A␤42, in response to highly selective ␥-secretase inhibitors has been observed in vivo in the plasma of guinea pigs (14) and in humans (15).…”
mentioning
confidence: 99%